Different risk factors are associated with alcohol use versus problematic use in male Pakistani adolescents. (27th August 2019) - Shahzad, Salman; Kliewer, Wendy; Ali, Muzaffar; Begum, Nasreen
Abstract : Substance abuse is a significant problem in Pakistan (Hussain, 2017), yet, there are few studies of risk factors in this population, particularly in remote areas. Male adolescents ( N  = 243; M  = 16.9 years, SD  = 1.3 years) were recruited from schools in Gilgit‐Baltistan, and completed questions on demographics, substance use, and psychosocial functioning. As a Muslim country, there are strict prohibitions against alcohol use, yet 44.9% of the sample reported lifetime alcohol use. The Alcohol Use Disorders Identification Test (Babor, Higgins‐Biddle, Saunders, & Monteiro, 2001), was used to quantify level of risk associated with use, and 22.6% of the sample had scores indicating significant risk levels. Logistic regression analyses indicated that lifetime alcohol use was associated with internalising problems (e.g., depression, anxiety), while risky alcohol use was associated with externalising problems (e.g., aggressive and delinquent behaviour). Attention problems were related to both outcomes. Implications for prevention are discussed.